Analysis of Skills and Knowledge of Dalmas Personnel Case Study at Polres Cianjur - Anjar Maulana; Basir S; Firman Fadillah (Budapest International Research and Critics University, 2022)
Security and public order are important in running the government. The National Police of the Republic of Indonesia (POLRI) is mandated by Law Number 9 of 1998 concerning the freedom to express opinions in public, to organize security demonstrations by ensuring security and public order in accordance with applicable procedures. Demonstration by the Cianjur Police. Based on the results of the West Java Police Propam field examination contained in the Disciplinary Violation Preliminary Examination file number: DP3D-13/K/II/HUK.12.10/2020/Bid-Propam and the police report with the number: LP/6-A/I/HUK. 12.10/2020/Bid-Propam. This study uses a qualitative method with a single case approach, this research approach has a case dissection perspective by looking at aspects of personnel competence when securing demonstrations so that the expected approach will bring the best results. Cianjur Police personnel who have implemented Dikbangspes associated with competency theory have resulted in the view that 6 (six) Cianjur Police personnel do not have the expertise (Dikjur) and skills (short training) in the field of technical functions of the Sabhara Unit police. Then, there are three policy makers (Head of Ops, Kasat Binmas, and KBO Sabhara) during the process of securing demonstrations, have long service experience, namely Head of Ops KOMPOL Warsito has served for 33 years, Head of Binmas AKP Achmad Suprijatna has served for 30 years, and KBO Sabhara has served for 28 years.